Alkali-resistant and anti-cracking exterior wall paint and preparation method thereof
The exterior wall paint formulation addresses issues of alkalinity and cracking by creating a stable, three-dimensional gel network structure using industrial waste materials, enhancing durability and mechanical properties while promoting sustainable production.
Patent Information
- Application Number
- CN202410937408.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-12
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-07-12
AI Technical Summary
Existing exterior wall paints face issues of high alkalinity, water absorption, and premature cracking due to high porosity and salt content, leading to reduced durability and aesthetic issues.
A formulation of exterior wall paint comprising high-lime blast furnace slag, metakaolin, coal ash, sodium silicate, and additives like silica nanoparticles, alkyl silane, and sulfurous compounds, which are mixed and processed to create a three-component system that enhances dispersion, reduces porosity, and promotes a stable, three-dimensional gel network structure.
The solution significantly improves the paint's resistance to cracking, alkalinity, and water absorption, resulting in enhanced mechanical properties and extended durability while utilizing industrial waste materials for sustainable and cost-effective production.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
[Technical field]
[0001] The invention relates to the technical field of coatings, and in particular to an alkali-resistant and crack-resistant exterior wall paint and a preparation method thereof. [Background technology]
[0002] Organic coatings with advantages such as good decorativeness and diversity have always occupied a dominant position in the domestic and international coatings markets. However, from the perspective of actual application, many organic exterior wall coatings will have various problems such as cracking and falling off after a period of time, which will greatly affect their aesthetic effect and protective effect on buildings. Compared with organic coatings, the film-forming substances of inorganic coatings are non-toxic, and the dispersion medium in most inorganic coatings is water rather than organic solvents. Such water-based inorganic coatings do not contain organic volatile substances. When damaged by high temperature, no toxic gases will be released. The film-forming mechanism of inorganic coatings is mainly to promote silicates to generate SiO2 gel, but the silica gel formed after curing has a high porosity, and the soluble salt and alkali content added during the preparation process is at a high level. Therefore, there are problems of high water absorption and easy alkali efflux. Coatings with high water absorption are prone to falling off and cracking, and alkali efflux coatings have poor color stability, which seriously affects the appearance quality and service life of the coating.
[0003] Blast furnace slag is solid waste produced during the blast furnace ironmaking process, so it is particularly important to reduce the amount of blast furnace slag and reuse it as a resource.
[0004] Therefore, providing an energy-saving and environmentally friendly exterior wall paint solution that is alkali-resistant and crack-resistant is an issue that needs to be urgently addressed. [Summary of the invention]
[0005] The technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide an alkali-resistant and anti-cracking exterior wall paint and a preparation method thereof.
[0006] The technical solution provided by the present invention can make up for the defects of the wall paint provided by the prior art, such as weak alkali resistance, easy cracking and environmental protection, etc., to a certain extent.
[0007] In order to achieve the above purpose, the following technical solutions are used:
[0008] An alkali-resistant and anti-cracking exterior wall paint comprising the following components by weight:
[0009] Slag: 50-100 parts
[0010] Kaolin: 400-450 parts
[0011] Fly ash powder: 200-250 parts
[0012] Calcium silicate: 20-50 parts
[0013] Sodium water glass: 300-360 parts
[0014] Hydroxypropyl methylcellulose: 10-20 parts
[0015] Polyvinyl alcohol: 10-20 parts
[0016] Zeolite: 2-6 parts
[0017] Dimethyl silicone oil: 40-60 parts
[0018] Nano-SiO2: 30-50 parts
[0019] Graphene oxide: 2-5 parts
[0020] Sulfurous acid: 30-60 parts.
[0021] The method for preparing the alkali-resistant and anti-cracking exterior wall paint comprises the following steps:
[0022] 1) Weigh the required raw materials according to the above weight components;
[0023] 2) Add the weighed polyvinyl alcohol and hydroxypropyl methylcellulose into a stirring disperser, add deionized water, adjust the motor speed to 1000-1500 rpm, and disperse for 10-30 minutes to obtain component A;
[0024] 3) Stir and mix the weighed kaolin, slag, fly ash powder, calcium silicate and zeolite, and grind for 1-3 hours to obtain component B;
[0025] 4) adding the weighed graphene oxide and water glass into a stirring disperser, adding deionized water, adjusting the motor speed to 800-1000 rpm, dispersing for 10-30 min, then adding the weighed nano-SiO2 and dimethyl silicone oil, dispersing for 10-30 min at 800-1000 rpm to obtain component C;
[0026] 5) Mix the above components A and B, and stir at 800-1000 rpm for 20-30 min. After stirring evenly, slowly add the mixture to the stirred component C, mix and stir for 30-60 min, let stand for 2-6 h, add sulfurous acid, mix and stir for 10-30 min to obtain the alkali-resistant and anti-cracking exterior wall paint.
[0027] Optionally, the hydroxypropyl methylcellulose is used as a thickener. Both the hydroxypropyl methylcellulose and the polyvinyl alcohol are commercially available industrial products. The addition of polyvinyl alcohol in the present invention can reduce the problem of fine cracks generated after the coating is cured.
[0028] Optionally, the fly ash powder is low-calcium fly ash powder with a specific surface area of 500-1200m2 / kg and an average particle size of 25μm.
[0029] Optionally, the slag is preferably high-calcium slag, and the slag is in powder form with a specific surface area of 500-1000m2 / kg and fine slag powder with a particle size of 10-20μm.
[0030] Optionally, the calcium silicate is hydrated calcium silicate, and commercially available spherical powder particles with a particle size of ≤100 nm are selected; the sodium water glass is a commercially available industrial sodium silicate aqueous solution, wherein the mass content of sodium oxide is 10-15%, the mass content of silicon dioxide is 25-29%, the solid content is 35-44%, and the remaining main component is water, and the modulus is 2.
[0031] Optionally, the kaolin is preferably high-activity metakaolin obtained after calcination.
[0032] Optionally, the fly ash, slag and kaolin described in the present invention are all selected from industrial solid waste, so as to realize resource utilization of industrial solid waste and meet the requirements of low carbon, energy saving and environmental protection.
[0033] The graphene oxide may be the graphene oxide conventionally used in the art, generally referring to graphite oxide obtained by oxidizing graphite by the HUMMMERS method, and then dispersed by ultrasonic wave to exfoliate the graphene oxide flakes.
[0034] Optionally, the zeolite is zeolite powder, which is processed into fine powder with a size of more than 600 mesh and less than 1200 mesh by a grinding machine, and the average particle size of the fine powder is 800 mesh. Adding the zeolite powder can not only absorb harmful formaldehyde gas, but the porous zeolite powder can also absorb salt and alkali ions, which is beneficial to reduce the occurrence of salt and alkali precipitation.
[0035] Optionally, the dimethyl silicone oil is terminal methyl polydimethylsiloxane, and the viscosity of the terminal methyl polydimethylsiloxane at 25° C. is 100 to 10000 mPa〃s; adding dimethyl silicone oil can improve the water absorption of the coating, increase the hydrophobicity of the coating, and reduce the shedding and cracking of the coating; the sulfurous acid is a commercially available analytical pure reagent product, CAS: 7782-99-2.
[0036] Optionally, the nano-SiO2 particle size is 5-50nm, and SD-5281 from Shengda Chemical is selected.
[0037] The beneficial effects of the present invention are:
[0038] 1. Since calcium silicate gel is generated quickly, the powder particles are wrapped in the coating before they are dispersed in time, resulting in large particle agglomeration, which prevents other reactions from taking place. The preparation process of this application adopts a three-component design, which can add the raw materials that cause rapid solidification separately, reduce the generation of agglomeration, and avoid the direct neutralization and dilution of alkaline substances before they start to react. The grouped preparation is conducive to a more complete and uniform sodium water glass reaction, thereby improving the performance of the coating.
[0039] 2. The surface of graphene has many functional groups. In the formed C component, the reaction solution formed by graphene oxide and water glass has a good dispersing effect, which can well solve the problem of uneven dispersion of nano-silica and dimethyl silicone oil in polymers, and can better exert the hydrophobic effect of nano-silica and dimethyl silicone oil. Water glass can reduce graphene oxide, and the structure of the reduced graphene changes to form folded graphene, which has a structure similar to a three-dimensional mesh structure, and has better crystallinity and many edge wrinkles, which is conducive to the induced nucleation and filling effect of nano-silica. Silica can rely on the above structure to promote the formation and extension of gel, and can form a unique three-dimensional gel network structure, which can fill the voids and microcracks of the matrix, reduce the porosity, improve the density and mechanical properties of the coating, thereby preventing the cracking of the coating.
[0040] 3. The present application finally adds sulfurous acid, and the metal oxide components such as calcium oxide and iron oxide in the fly ash powder and the mineral can react with it to generate insoluble substances such as sulfites. These insoluble substances will act as crystal nuclei to accelerate the coagulation and solidification of the gel product, thereby promoting the structural development of the gel product. The addition of sulfurous acid also changes the integrity and density of the mineral particles from the outside to the inside, and can produce more pores inside the particles, increase the specific surface area of the mineral particles, so that a large number of free salt and alkali ions inside the coating are adsorbed and fixed inside the mineral particles, preventing them from migrating to the surface of the coating, thereby improving the alkali resistance. Due to the weak acidity of sulfurous acid, the destruction of the gel structure is limited. Compared with strong acid, it can reduce the loss of activity of mineral components. While being able to react with excess hydroxide ions to reduce the pH value of the system, it will not change the alkaline environment, which is conducive to the stable formation of the gel.
[0041] 4. The main raw materials of the wall paint of the present invention are selected from coal ash and slag from industrial solid waste, which can achieve the reduction and resource reuse of blast furnace slag, realize green energy saving and environmental protection, and have low preparation cost. The obtained wall paint has very significant anti-cracking and anti-alkali effects and can be widely used.
[0042] Additional aspects and advantages of the present invention will be given in part in the following description, will become apparent from the following description, or may be learned through embodiments of the present invention. [Specific implementation method]
[0043] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Other embodiments obtained by those skilled in the art without making any creative ideas belong to the scope of protection of the present invention.
[0044] In the embodiment of the present invention, the quality of each component of the alkali-resistant and crack-resistant exterior wall paint can effectively ensure the alkali-resistant and crack-resistant performance, as well as the dispersion stability and film-forming effect of the paint, which is conducive to the paint forming an alkali-resistant and crack-resistant coating on the exterior wall.
[0045] Embodiment 1:
[0046] Alkali-resistant and anti-cracking exterior wall paint: including the following components by weight:
[0047] Slag: 70 parts
[0048] Kaolin: 400 parts
[0049] Coal ash powder: 200 parts
[0050] Calcium silicate: 30 parts
[0051] Sodium water glass: 300 parts
[0052] Hydroxypropyl methylcellulose: 10 parts
[0053] Polyvinyl alcohol: 10 parts
[0054] Zeolite: 5 parts
[0055] Dimethyl silicone oil: 50 parts
[0056] Nano-SiO2: 45 parts
[0057] Graphene oxide: 4 parts
[0058] Sulfurous acid: 35 parts.
[0059] The method for preparing the alkali-resistant and anti-cracking exterior wall paint comprises the following steps:
[0060] 1) Weigh the required raw materials according to the above weight components
[0061] 2) Add the weighed polyvinyl alcohol and hydroxypropyl methylcellulose into a stirring disperser, add deionized water, adjust the motor speed to 1000 rpm, and disperse for 20 minutes to obtain component A;
[0062] 3) Stir and mix the weighed kaolin, slag, fly ash powder, calcium silicate and zeolite, and grind for 3 hours to obtain component B;
[0063] 4) Add the weighed graphene oxide and water glass into a stirring disperser, add deionized water, adjust the motor speed to 1000 rpm, disperse for 30 min, then add the weighed nano-SiO2 and dimethyl silicone oil, and disperse for 30 min at 1000 rpm to obtain component C;
[0064] 5) Mix the above components A and B, stir at 800 rpm for 20 min, and then slowly add the mixture to the stirred component C after stirring evenly, mix and stir for 60 min, add sulfite reagent after standing for 5 h, and mix and stir for 30 min to obtain alkali-resistant and anti-cracking exterior wall paint.
[0065] Embodiment 2:
[0066] An alkali-resistant and anti-cracking exterior wall paint comprising the following components by weight:
[0067] Slag: 80 parts
[0068] Kaolin: 450 parts
[0069] Fly ash powder: 250 parts
[0070] Calcium silicate: 50 parts
[0071] Sodium water glass: 360 parts
[0072] Hydroxypropyl methylcellulose: 20 parts
[0073] Polyvinyl alcohol: 20 parts
[0074] Zeolite: 3 parts
[0075] Dimethyl silicone oil: 40 parts
[0076] Nano-SiO2: 50 parts
[0077] Graphene oxide: 5 parts
[0078] Sulfurous acid: 60 parts.
[0079] The method for preparing the alkali-resistant and anti-cracking exterior wall paint comprises the following steps:
[0080] 1) Weigh the required raw materials according to the above weight components
[0081] 2) Add the weighed polyvinyl alcohol and hydroxypropyl methylcellulose into a stirring disperser, add deionized water, adjust the motor speed to 1200 rpm, and disperse for 20 minutes to obtain component A;
[0082] 3) Stir and mix the weighed kaolin, slag, fly ash powder, calcium silicate and zeolite, and grind for 3 hours to obtain component B;
[0083] 4) Add the weighed graphene oxide and water glass into a stirring disperser, add deionized water, adjust the motor speed to 9000 rpm, disperse for 25 minutes, then add the weighed nano-SiO2 and dimethyl silicone oil, and disperse for 20 minutes at 800 rpm to obtain component C;
[0084] 5) Mix the above components A and B, stir at 800 rpm for 20 min, and then slowly add the mixture to the stirred component C after stirring evenly, mix and stir for 60 min, add sulfurous acid after standing for 4 h, and mix and stir for 25 min to obtain the alkali-resistant and anti-cracking exterior wall paint.
[0085] Example 3
[0086] An alkali-resistant and anti-cracking exterior wall paint comprising the following components by weight:
[0087] Slag: 75 parts
[0088] Kaolin: 420 parts
[0089] Fly ash powder: 245 parts
[0090] Calcium silicate: 40 parts
[0091] Sodium water glass: 350 parts
[0092] Hydroxypropyl methylcellulose: 15 parts
[0093] Polyvinyl alcohol: 10 parts
[0094] Zeolite: 6 parts
[0095] Dimethyl silicone oil: 60 parts
[0096] Nano-SiO2: 38 parts
[0097] Graphene oxide: 3 parts
[0098] Sulfurous acid: 45 parts.
[0099] The method for preparing the alkali-resistant and anti-cracking exterior wall paint comprises the following steps:
[0100] 1) Weigh the required raw materials according to the above weight components
[0101] 2) Add the weighed polyvinyl alcohol and hydroxypropyl methylcellulose into a stirring disperser, add deionized water, adjust the motor speed to 1000 rpm, and disperse for 10 minutes to obtain component A;
[0102] 3) Stir and mix the weighed kaolin, slag, fly ash powder, calcium silicate and zeolite, and grind for 3 hours to obtain component B;
[0103] 4) Add the weighed graphene oxide and water glass into a stirring disperser, add deionized water, adjust the motor speed to 800 rpm, disperse for 30 min, then add the weighed nano-SiO2 and dimethyl silicone oil, and disperse for 30 min at 1000 rpm to obtain component C;
[0104] 5) Mix the above components A and B, stir at 1000 rpm for 20 min, and then slowly add the mixture to the stirred component C after stirring evenly, mix and stir for 60 min, add sulfurous acid after standing for 5 h, and mix and stir for 30 min to obtain the alkali-resistant and anti-cracking exterior wall paint.
[0105] Comparative Example 1:
[0106] Exterior wall paint: including the following components by weight:
[0107] Slag: 80 parts
[0108] Kaolin: 450 parts
[0109] Fly ash powder: 250 parts
[0110] Calcium silicate: 50 parts
[0111] Sodium water glass: 360 parts
[0112] Hydroxypropyl methylcellulose: 20 parts
[0113] Polyvinyl alcohol: 20 parts
[0114] Zeolite: 3 parts
[0115] Dimethyl silicone oil: 40 parts
[0116] Graphene oxide: 5 parts
[0117] Sulfurous acid: 60 parts.
[0118] The exterior wall paint preparation method comprises the following steps:
[0119] 1) Weigh the required raw materials according to the above weight components
[0120] 2) Add the weighed polyvinyl alcohol and hydroxypropyl methylcellulose into a stirring disperser, add deionized water, adjust the motor speed to 1200 rpm, and disperse for 20 minutes to obtain component A;
[0121] 3) Stir and mix the weighed kaolin, slag, fly ash powder, calcium silicate and zeolite, and grind for 3 hours to obtain component B;
[0122] 4) Add the weighed graphene oxide and water glass into a stirring disperser, add deionized water, adjust the motor speed to 9000 rpm, disperse for 25 minutes, then add the weighed dimethyl silicone oil, and disperse for 20 minutes at 800 rpm to obtain component C;
[0123] 5) Mix the above components A and B, stir at 800 rpm for 20 min, and then slowly add the mixture to the stirred component C after stirring evenly, mix and stir for 60 min, let stand for 4 h, add sulfurous acid, mix and stir for 25 min to obtain the exterior wall paint.
[0124] Comparative Example 2
[0125] Exterior wall paint: including the following components by weight:
[0126] Slag: 80 parts
[0127] Kaolin: 450 parts
[0128] Fly ash powder: 250 parts
[0129] Calcium silicate: 50 parts
[0130] Sodium water glass: 360 parts
[0131] Hydroxypropyl methylcellulose: 20 parts
[0132] Polyvinyl alcohol: 20 parts
[0133] Zeolite: 3 parts
[0134] Dimethyl silicone oil: 40 parts
[0135] Nano-SiO2: 50 parts
[0136] Sulfurous acid: 60 parts.
[0137] The exterior wall paint preparation method comprises the following steps:
[0138] 1) Weigh the required raw materials according to the above weight components
[0139] 2) Add the weighed polyvinyl alcohol and hydroxypropyl methylcellulose into a stirring disperser, add deionized water, adjust the motor speed to 1200 rpm, and disperse for 20 minutes to obtain component A;
[0140] 3) Stir and mix the weighed kaolin, slag, fly ash powder, calcium silicate and zeolite, and grind for 3 hours to obtain component B;
[0141] 4) Add the weighed water glass into a stirring disperser, add deionized water, adjust the motor speed to 9000 rpm, disperse for 25 minutes, then add the weighed nano-SiO2 and dimethyl silicone oil, and disperse for 20 minutes at 800 rpm to obtain component C;
[0142] 5) Mix the above components A and B, stir at 800 rpm for 20 min, and then slowly add the mixture to the stirred component C after stirring evenly, mix and stir for 60 min, let stand for 4 h, add sulfurous acid, mix and stir for 25 min to obtain the exterior wall paint.
[0143] Comparative Example 3:
[0144] Exterior wall paint: including the following components by weight:
[0145] Slag: 75 parts
[0146] Kaolin: 420 parts
[0147] Fly ash powder: 245 parts
[0148] Calcium silicate: 40 parts
[0149] Sodium water glass: 350 parts
[0150] Hydroxypropyl methylcellulose: 15 parts
[0151] Polyvinyl alcohol: 10 parts
[0152] Zeolite: 6 parts
[0153] Dimethyl silicone oil: 60 parts
[0154] Nano-SiO2: 38 parts
[0155] Graphene oxide: 3 parts.
[0156] The exterior wall paint preparation method comprises the following steps:
[0157] 1) Weigh the required raw materials according to the above weight components
[0158] 2) Add the weighed polyvinyl alcohol and hydroxypropyl methylcellulose into a stirring disperser, add deionized water, adjust the motor speed to 1000 rpm, and disperse for 10 minutes to obtain component A;
[0159] 3) Stir and mix the weighed kaolin, slag, fly ash powder, calcium silicate and zeolite, and grind for 3 hours to obtain component B;
[0160] 4) Add the weighed graphene oxide and water glass into a stirring disperser, add deionized water, adjust the motor speed to 800 rpm, disperse for 30 min, then add the weighed nano-SiO2 and dimethyl silicone oil, and disperse for 30 min at 1000 rpm to obtain component C;
[0161] 5) Mix the above components A and B, stir at 1000 rpm for 20 min, and then slowly add the mixture into the stirred component C after stirring evenly, and mix and stir for 60 min to obtain the exterior wall paint.
[0162] Comparative Example 4:
[0163] Exterior wall paint: including the following components by weight:
[0164] Slag: 75 parts
[0165] Kaolin: 420 parts
[0166] Fly ash powder: 245 parts
[0167] Calcium silicate: 40 parts
[0168] Sodium water glass: 350 parts
[0169] Hydroxypropyl methylcellulose: 15 parts
[0170] Polyvinyl alcohol: 10 parts
[0171] Zeolite: 6 parts
[0172] Nano-SiO2: 38 parts
[0173] Graphene oxide: 3 parts
[0174] Sulfurous acid: 45 parts.
[0175] The exterior wall paint preparation method comprises the following steps:
[0176] 1) Weigh the required raw materials according to the above weight components
[0177] 2) Add the weighed polyvinyl alcohol and hydroxypropyl methylcellulose into a stirring disperser, add deionized water, adjust the motor speed to 1000 rpm, and disperse for 10 minutes to obtain component A;
[0178] 3) Stir and mix the weighed kaolin, slag, fly ash powder, calcium silicate and zeolite, and grind for 3 hours to obtain component B;
[0179] 4) Add the weighed graphene oxide and water glass into a stirring disperser, add deionized water, adjust the motor speed to 800 rpm, disperse for 30 min, then add the weighed nano-SiO2, and disperse for 30 min at 1000 rpm to obtain component C;
[0180] 5) Mix the above components A and B, stir at 1000 rpm for 20 min, and then slowly add the mixture to the stirred component C after stirring evenly, mix and stir for 60 min, let stand for 5 h, add sulfurous acid, mix and stir for 30 min to obtain the exterior wall paint.
[0181] Comparative Example 5:
[0182] Exterior wall paint: including the following components by weight:
[0183] Slag: 75 parts
[0184] Kaolin: 420 parts
[0185] Fly ash powder: 245 parts
[0186] Calcium silicate: 40 parts
[0187] Sodium water glass: 350 parts
[0188] Hydroxypropyl methylcellulose: 15 parts
[0189] Polyvinyl alcohol: 10 parts
[0190] Zeolite: 6 parts
[0191] Dimethyl silicone oil: 60 parts
[0192] Nano-SiO2: 38 parts
[0193] Graphene oxide: 3 parts
[0194] Sulfurous acid: 45 parts.
[0195] The method for preparing the alkali-resistant and anti-cracking exterior wall paint comprises the following steps:
[0196] 1) Weigh the required raw materials according to the above weight components;
[0197] 2) Add the weighed raw materials into a stirring disperser in sequence, add deionized water, adjust the motor speed to 1000 rpm, mix and disperse for 60 minutes to obtain the wall paint.
[0198] All the obtained products were tested for performance using the standard test of JG / T 26-2002 "Exterior Inorganic Architectural Coatings", and the anti-efflorescence performance test was performed with reference to the national standard JC / T1024-2007 "Wall Finishing Mortar". The test results in Examples 1-3 are shown in Table 1:
[0199]
[0200]
[0201] The test results in Comparative Examples 1-5 are shown in Table 2:
[0202]
[0203]
[0204] It can be seen from the test results in Table 1 above that the exterior wall paints in Examples 1-3 of the present invention have efficient alkali resistance and anti-cracking effects, and the test results are far better than the specified index values. First, the wall paint is prepared in groups during the preparation process, which can avoid the phenomenon of large particle agglomeration caused by the powder particles being wrapped in the paint before they are dispersed in time, and also prevent the alkali that has not yet started to react from being neutralized by the acid, thereby preventing other reactions from proceeding; secondly, SiO2, dimethyl silicone oil, and graphene reagent are added to the present invention, and the solution after the reaction of SiO2, dimethyl silicone oil and water glass-graphene is mixed, which not only solves the problem of uneven dispersion of nano-silicon dioxide and dimethyl silicone oil in polymers, but also exerts the hydrophobic effect of nano-silicon dioxide and dimethyl silicone oil. At the same time, water glass can reduce graphene oxide, and the structure of the reduced graphene changes to form folded graphene, which can promote the induced nucleation of nano-silicon dioxide and the filling effect. Silica can rely on the above structure to promote gel formation and extension to form a unique three-dimensional gel network The network structure fills the voids and microcracks of the matrix, improves the density and mechanical properties of the coating, thereby preventing the coating from cracking. The mechanical properties of graphene oxide itself and the hydrophobic effect of nano-silica and dimethyl silicone oil can also improve the anti-fouling ability and anti-scouring ability by introducing it into the raw materials of wall paint; finally, the present application adds sulfurous acid in the fifth step, which can not only react with the existing metal oxide to generate a pro-gel substance, but also increase the specific surface area and porous structure of the gel, improve the adsorption effect of saline ions, and reduce the surface migration probability of the above ions. Usually, saline ions migrate with free water, combined with the hydrophobic effect of nano-silica and dimethyl silicone oil, the synergistic effect of the above substances greatly reduces the occurrence of alkali efflux, and the addition of sulfurous acid will not affect the gel structure, that is, while improving the anti-alkali performance, it can also ensure the mechanical strength of the coating. It can also be seen from Table 1 above that the mechanical properties in Examples 1-3 are better than the index values, and no visible alkali efflux occurs.
[0205] However, the performance of comparative examples 1-5 has declined to varying degrees. It can be seen from the results of comparative examples 1-2 and 4 that the synergistic effect of the nano-SiO2, dimethyl silicone oil and graphene reagent added in the present application makes the coating have excellent anti-cracking, anti-fouling and anti-aging properties. It can be seen from the results of comparative example 3 that sulfurous acid plays a great role in anti-alkali effect; in comparative example 5, the wall paint showed agglomeration and caking phenomenon, and the coating performance showed a significant decline. The water glass can directly react with sulfurous acid during mixing, so that both lose their effects. Therefore, the preparation method of the components in the present application can well avoid agglomeration and destruction of the alkaline environment required for gel growth. The main raw materials of the wall paint of the present invention are selected from coal ash and slag from industrial solid waste, which can achieve the reduction and resource reuse of blast furnace slag, realize green energy saving and environmental protection, and have low preparation cost. The obtained wall paint not only has very significant effects such as anti-cracking and anti-alkali, but also has anti-fouling and aging resistance, and can be widely used.
[0206] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing an alkali-resistant and anti-cracking exterior wall paint, the alkali-resistant and anti-cracking exterior wall paint comprising the following components by weight: Slag: 50-100 parts Kaolin: 400-450 parts Fly ash powder: 200-250 parts Calcium silicate: 20-50 parts Sodium water glass: 300-360 parts Hydroxypropyl methylcellulose: 10-20 parts Polyvinyl alcohol: 10-20 parts Zeolite: 2-6 parts Dimethyl silicone oil: 40-60 parts Nano-SiO2: 30-50 parts Graphene oxide: 2-5 parts Sulfurous acid: 30-60 parts; The preparation method of the alkali-resistant and anti-cracking exterior wall paint comprises the following steps: 1) Weigh the required raw materials according to the above weight components; 2) Add the weighed polyvinyl alcohol and hydroxypropyl methylcellulose into a stirring disperser, add deionized water, adjust the motor speed to 1000-1500 rpm, and disperse for 10-30 minutes to obtain component A; 3) Mix the weighed kaolin, slag, fly ash powder, calcium silicate and zeolite, and grind for 1-3 hours to obtain component B; 4) Add the weighed graphene oxide and water glass into a stirring disperser, add deionized water, adjust the motor speed to 800-1000 rpm, disperse for 10-30 minutes, then add the weighed nano-SiO2 and dimethyl silicone oil, disperse for 10-30 minutes at 800-1000 rpm to obtain component C; 5) Mix the above components A and B, stir at 800-1000 rpm for 20-30 min, and then slowly add the mixture to the stirred component C after stirring evenly, mix and stir for 30-60 min, let stand for 2-6 h, then add sulfurous acid, and mix and stir for 10-30 min to obtain the alkali-resistant and crack-resistant exterior wall paint.
2. The method for preparing the alkali-resistant and anti-cracking exterior wall paint according to claim 1, characterized in that: The slag is high calcium slag, and the high calcium slag has a specific surface area of 500-1000m 2 / kg, fine slag powder with particle size of 10-20μm.
3. The method for preparing the alkali-resistant and anti-cracking exterior wall paint according to claim 1, characterized in that: The fly ash powder is low-calcium fly ash powder, and the specific surface area of the low-calcium fly ash powder is 500-1200m 2 / kg, and the average particle size is 25μm.
4. The method for preparing the alkali-resistant and anti-cracking exterior wall paint according to claim 1, characterized in that: The calcium silicate is hydrated calcium silicate powder particles with a particle size of ≤100 nm.
5. The method for preparing the alkali-resistant and anti-cracking exterior wall paint according to claim 1, characterized in that: The sodium water glass is a sodium silicate aqueous solution, in which the mass content of sodium oxide is 10-15%, the mass content of silicon dioxide is 25-29%, the solid content is 35-44%, and the remaining main component is water. The modulus is 2.
6. The method for preparing the alkali-resistant and anti-cracking exterior wall paint according to claim 5, characterized in that: The zeolite is zeolite fine powder processed by a grinding machine to a size of 600 mesh or more and 1200 mesh or less.
Citation Information
Patent Citations
Modified magnesium sulfate cement and preparation method thereof
CN109503009A
Inorganic thermal-insulation fireproof hydrophobic coating and preparation method thereof
CN111019417A
Water-based silicate inorganic coating and preparation method thereof
CN111826010A
Method for preparing inorganic waterproof coating through alkali-activated mineral powder activity
CN112126259A
Cited By
Highly permeable alkali-resistant nitrate coating and preparation method thereof
CN122521189A